454 Study in progress: international retrospective study on lymphadenectomy in endometrioid ovarian carcinoma patients with early stage disease (LEOPARD). (13th November 2020) - Krämer, P; Grube, M; Renno, T; Brar, H; McAlpine, JN; de Kroon, CD; Heitz, F; Heublein, S; Manchanda, R; Plante, M; Bachvarov, D; Zeimet, AG; et al.
Abstract : Introduction: The benefit of systematic lymphadenectomy (LNE) in low-stage, low-grade ovarian carcinoma is unknown. However, most guidelines still recommend LNE in these patients. Prior studies examining the benefit of this invasive procedure have been hampered small numbers, and large-scale studies that consider modern classification are needed. Methods: A cohort of 666 pathology-reviewed and immunohistochemistry-validated endometrioid ovarian carcinomas has recently been evaluated using endometrial carcinoma-inspired molecular subtyping. This molecularly characterized series is now being used to assess the value of LNE. Contributing centers are performing detailed chart reviews, so that surgical procedures and lymph node status can be correlated with molecular subtype and outcomes. Results: 349 stage I, 181 stage II, 85 stage III, and 22 stage IV cases with a median OS follow-up of 6.11 years (RevKM) were collected from 17 centres across Canada and Europe. Analysis of the first 70/666 cases revealed positive nodes in only a single presumed low stage patient after systematic pelvic and paraaortic LNE (n=1/44). LNE was not performed in 3/44 and restricted to pelvic nodes in 6/44 low-stage cases, all of which were pN0. Tumor spread beyond the Uterus and/or Adnexa was associated with positive nodes in 33%. Conclusion: Preliminary results indicate that abandonment of LNE in low-stage, low-grade endometrioid ovarian carcinoma may reduce morbidity without worsening prognosis for these patients. Completion and expansion of our international team initiative stands to provide a powerful statement on the value of LNE, and influence of molecular subtype on disease spread, possibly improving precision care for ovarian carcinoma patients.